Injectable Aorta Tissue Paste for Vocal Fold Medialization: Residence Time, Biocompatibility, and Comparison to Predicates in a Guinea Pig Subdermal Model. (November 2016) - Burns, James A.; Botelho, Jaime L.; Bell, Jonathan I.; Faquin, William; Lopez-Guerra, Gerardo; Ackerman, Jerome L.; Kobler, James B.
Objectives: Aortic homografts integrate well with laryngeal tissue when used in reconstructive surgery. It was hypothesized that a paste of aortic homograft, rich in slow-to-degrade elastin, would compare favorably in residence time and biocompatibility to predicate materials used for vocal fold injection-medialization. Methods: An injectable aorta paste (AP) was made by pulverizing aortic homografts at −196°C (cryomilling). To assess residence time and biocompatibility, 0.3 cc was injected subdermally in guinea pigs (n = 3 per 2-, 4-, 8-, 16-, 24-week time points) followed by histological analysis. To test particle size versus residence time, APs made using 80 or 200 seconds of cryomilling were compared. Implant characteristics of AP were then compared to Restylane, Radiesse Voice (Hydroxylapatite), Radiesse Voice Gel, and Cymetra in additional animals (n = 6 per 4-, 8-, 12-week time points). Results: Injected AP formed ovoid masses with minimal inflammation. Cellular infiltration was mild and increased with survival time. There was a gradual reduction of implant volume to ~40% at 24 weeks. Increased residence time for paste with larger particles (80 cryomilling seconds) was noted. Von Kossa staining showed progressive calcification of the AP. Cymetra was difficult to reconstitute reliably but formed subdermal masses similar to AP in shape, size, and reactivity and without calcification. The other predicates showed good biocompatibility but spread more widely and erratically in the tissue. Conclusion: Aortic paste is easy to create, biocompatible, degrades slowly, and forms well-defined implants in guinea pig subdermal tissue. The AP implants calcified over time, and experiments are ongoing to determine the source of calcification and how it might be controlled or exploited clinically.